ON DECOMPOSITIONS OF NORMED UNITS IN ABELIAN GROUP RINGS - Danchev, Peter (IndoMS, 2012)
We strengthen some results of W. L. May (J. Algebra, 1976) by findinga criterion when a special decomposition of normed units in abelian group ringsholds.DOI :Â http://dx.doi.org/10.22342/jims.18.1.106.21-29